Efektivitas Penginjilan Digital sebagai Media dan Tantangan dalam Pemuridan Generasi Muda - Anwar Jenris Tana; Milton T. Pardosi (JUITAK: Jurnal Ilmiah Teologi dan Pendidikan Kristen, 2024)
AbstractDigitalization has had a significant impact on various aspects of life, including in the realm of business and religious practices. This research focuses on Christian evangelism in the digital era, where technology has become an integral tool for spreading religious teachings. Digitalization allows churches and religious organizations to leverage social media, websites, podcasts, and other online platforms to reach a wider audience, significantly younger generations increasingly connected to technology. This research uses literature analysis methods and phenomenon observation as the primary approach. The research results show that digital evangelism effectively reaches a broader audience but is also faced with challenges, such as the risk of spreading misinformation or religious extremism. The importance of ethical responsibility in using technology is highlighted, with the need for churches and spiritual leaders to develop discipleship strategies that are contextual and responsive to current developments.